2014
DOI: 10.4088/jcp.14m09416
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone Palmitate Once-Monthly Reduces Risk of Relapse of Psychotic, Depressive, and Manic Symptoms and Maintains Functioning in a Double-Blind, Randomized Study of Schizoaffective Disorder

Abstract: Objective: Schizoaffective disorder is a complex illness for which optimal treatment is not well established. Results of the first controlled, relapse-prevention study of paliperidone palmitate once-monthly injectable (paliperidone monthly) in schizoaffective disorder are presented. Method:The study was conducted between September 20, 2010, and October 22, 2013. Patients with schizoaffective disorder (confirmed by the Structured Clinical Interview for DSM-IV Axis I Disorders) experiencing acute exacerbation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 28 publications
4
63
1
Order By: Relevance
“…[1,14,15] Possibilities of preventive treatment expanded considerably after the introduction of mood stabilizers (MSs). [1,3,19] The preference is currently given to atypical antipsychotic medications which have a mood stabilizing effect in addition to an antipsychotic one. [16,17,20] The most frequently prescribed are second-generation antipsychotics, but the high cost and side effects (weight gain and sexual dysfunction) lead to patients with SAD abandoning treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,14,15] Possibilities of preventive treatment expanded considerably after the introduction of mood stabilizers (MSs). [1,3,19] The preference is currently given to atypical antipsychotic medications which have a mood stabilizing effect in addition to an antipsychotic one. [16,17,20] The most frequently prescribed are second-generation antipsychotics, but the high cost and side effects (weight gain and sexual dysfunction) lead to patients with SAD abandoning treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Articles dedicated to SAD treatment in the interictal period are rare. [9,20] In most studies, SAD patients are often combined into one group along with schizophrenia patients or less commonly with those suffering from affective disorders, [18][19][20] which makes it difficult to obtain data about the peculiarities of SAD treatment. Therefore, it became necessary to investigate the influence of different types of therapy on the quality of remission in schizoaffective disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The 15-month, randomized, double-blind, placebocontrolled, parallel-group study of paliperidone palmitate evaluating time to relapse in subjects with schizoaffective disorder investigated the efficacy, safety, and tolerability of the once-monthly, atypical, long-acting, antipsychotic, paliperidone palmitate compared with placebo in the delay of relapse of the symptoms of schizoaffective disorder 11,12 . This long-term study demonstrated that paliperidone palmitate treatment at doses of 78-234 mg significantly delayed relapse and reduced risk of relapse in patients with schizoaffective disorder 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…n this issue of The Journal of Clinical Psychiatry, Fu et al 1 report on the results of a study of paliperidone palmitate once-monthly in patients diagnosed with schizoaffective disorder. In this well-designed and well-executed trial, paliperidone monthly was used either as monotherapy or as an adjunct to mood stabilizers or antidepressants.…”
mentioning
confidence: 99%
“…One of the interesting elements of Fu and colleagues' study 1 is the separation of the subjects into a group that could be treated with paliperidone monthly alone and a group who were already established prestudy on mood stabilizers and antidepressants and were allowed to remain on them. The investigators understood that schizoaffective disorder is often treated with multiple drugs.…”
mentioning
confidence: 99%